Tour-based Orestad Traffic Passenger Demand Model - Jovicic, Goran; Hansen, Christian Overgaard (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
Passenger travel demand model for greater Copenhagen area is a nested logit model where at the top of the tree is a generation model, below that is a distribution model and finally at the bottom is placed a mode choice model. The models are connected via logsums. The model is tour-based while in the previous version it was trip-based. The shift of the model paradigm from trip-based to tour-based proved to give improvements in model forecasts because some interactions between the trips that are included in a tour are now been captured in the model structure.